Responsibility Attitudes Assessment Instrument for Integrated Thematic Learning of Grade III - Radia, Elvira Hoesein; Wulandari, Aulia Ika (LPPM Undiksha, 2021)
Lack of assessment instruments and responsibilities in integrated thematic learning for grade III elementary schools. The teacher only observes students' attitudes so that they do not have a complete and valid picture. Based on these findings, the research objective of this study was to produce an assessment of the attitude of responsibility for integrated thematic learning theme 4 sub-theme 1 learning 5 grade III elementary school. This type of research is development research that refers to the theory of Borg and Gall by applying the ADDIE development model. The population of this research is third-grade students. The sample was determined using a random sampling technique with a selection of 23 students. The data collection technique used is an instrument in the form of a questionnaire using a Likert scale. The results showed that the social attitude instrument obtained data from 30 (thirty) statement items. The reliability of the integrated thematic learning responsibility assessment instrument theme 4 sub-theme 1 learning 5 grade III elementary school shows α = 0.759 then the instrument is in the reliable category. The instrument's validity level shows the lowest rcount is 0.411, has a Pearson Correlation XTot ≥ 0,3961 so that the instrument is categorized as valid and feasible to use. By using this assessment instrument, teachers can describe and measure students' attitudes of responsibility. In addition, teachers also assess to consistently assess the standard of student attitudes in the learning process and finding an accurate picture of student attitudes will provide feedback to students.